2018
DOI: 10.24099/vet.arhiv.170215
|View full text |Cite
|
Sign up to set email alerts
|

The effect of training and the Alka competition on oxidative stress and metabolic parameters in two horse breeds

Abstract: The aim of this study was to investigate the effects of training and the Alka competition upon the activity/ concentrations of antioxidative and muscle enzymes and metabolic parameters, as well as their correlations, in the serum of Thoroughbred (TH) and Croatian Warmblood (CWH) horses. The experiment was carried out on nine THs and seven CWHs. Blood samples were collected 30, 21 and 14 days before the Alka competition, immediately after the competition, and 7 days after. Serum concentrations of malondialdehyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Physical exercise can cause oxidative stress. Several studies showed that the pathogenesis of exercise-induced myopathies and inflammation in horses may be related the reactive oxidative species (ROS) generated during different kinds of effort [16,17]. ROS may damage not only the basic cellular structure but may also cause DNA damage [18].…”
Section: Introductionmentioning
confidence: 99%
“…Physical exercise can cause oxidative stress. Several studies showed that the pathogenesis of exercise-induced myopathies and inflammation in horses may be related the reactive oxidative species (ROS) generated during different kinds of effort [16,17]. ROS may damage not only the basic cellular structure but may also cause DNA damage [18].…”
Section: Introductionmentioning
confidence: 99%